Burning mouth syndrome as a trigeminal small fibre neuropathy: Increased heat and capsaicin receptor TRPV1 in nerve fibres correlates with pain score. - Yilmaz, Z; Renton, T; Yiangou, Y; Zakrzewska, J; Chessell, I; Bountra, C; Anand, P (2007)
Burning mouth syndrome (BMS) is often an idiopathic chronic and intractable pain condition, affecting 1.5-5.5% of middle-aged and elderly women. We have studied the heat and capsaicin receptor TRPV1, and its regulator nerve growth factor (NGF), in BMS. Patients with BMS (n=10) and controls (n=10) were assessed for baseline and post-topical capsaicin pain scores, and their tongue biopsies immunostained for TRPV1, NGF, and structural nerve markers neurofilament and peripherin. Nerve fibres penetrating the epithelium were less abundant in BMS (p<0.0001), indicating a small fibre neuropathy. TRPV1-positive fibres were overall significantly increased in BMS (p=0.0011), as were NGF fibres (p<0.0001) and basal epithelial cell NGF staining (p<0.0147). There was a significant correlation between the baseline pain score and TRPV1 (p=0.0143) and NGF fibres (p=0.0252). A significant correlation was observed between baseline and post-capsaicin pain (p=0.0006). Selective TRPV1 and NGF blockers may provide a new therapy for BMS.